Aquilo que não pode desaparecer: um estudo sobre os casos clínicos de Medard Boss com vistas à explicitação do trabalho clínico daseinsanalítico - Ribeiro, Rafael Monho Pinto (2023)
Phenomenological thinking teaches us to let phenomena reveal themselves. Returning to the initial path of this thinking, the present work sought to make notes on Clinical Daseinsanalyse from the analysis of clinical cases by Medard Boss. To this end, we carried out a brief study on the history of phenomenological thought and on the foundations of Clinical Daseinsanalyse, then we presented six cases and four clinical vignettes and analyzed them with a view to the phenomenological dynamics related to each case and the clinical work of the psychotherapist. We obtained a meticulous analysis that made it possible to make notes about the cause and the clinical understanding of the psychotherapist according to their comprehensive guidelines, their focus of attention and their phenomenal horizon. As a result, in addition to observations that revealed the north of clinical work with a Daseinsanalytic orientation, the complex movement of that which for patients in the psychological clinic simply cannot disappear and requires unveiling and correspondence was made explicit. Thus, such unveiling and corresponding to the phenomena that come to the encounter proved, through the study of clinical cases, fundamental for the free relationship consonant with being-healthy. This work was carried out with the support of the Coordination for the Improvement of Higher Education Personnel – Brazil (CAPES)